(untitled) (Research, Society and Development, 2020)
The organization-worker relationship has revealed quite changeable characteristics with regard to its management processes in the social, economic and human dimension in the labor world and its dynamic organization-work-individual-productivity. Thus, such issues have boosted both the work environment and the work policy, making it important to observe and evaluate the adoption of new standards and behaviors in the workplace. It is in this sense that the present study sought to verify the influence of social anomie on organizational anomie. This is a quantitative research, of a correlational type, with 282 employees, mostly from a private company in the city of Rio de Janeiro-RJ, between 18 and 68 years old, the majority were women, as well, the higher education course presented a greater percentage, the largest were single and had no children. They answered Srole’s social anomie scale, the organizational anomie scale and a questionnaire where sociodemographic data were requested. Confirmatory factor analysis revealed that the instruments were reliable and trustworthy. There was a positive influence of social anomie on organizational anomie and on ANOVA, the higher the social anomie, the higher the score on organizational anomie. It is concluded that the organizational processes do not exist in an isolated way in an organization. Such understanding offers a new perspective for research and intervention in the organizational context, highlighting the organization’s culture as an important phenomenon to be evaluated in human behavior in organizations.